Positron emission tomography/magnetic resonance imaging in head and neck carcinoma: A brief review of literature - Sonam Khurana; Dhruv Khurana (Wolters Kluwer Medknow Publications, 2017)
The carcinoma in head and neck region is the sixth most common worldwide cancer. Various advanced technologies are used for the diagnosis and staging of tumor and magnetic resonance imaging (MRI) and positron emission tomography (PET) scan are two such modalities. MRI provides information about anatomical and functional characteristics of tumor and PET scan provides metabolic and molecular information of tumor. The information obtained by PET/computed tomography (CT) and MRI is complementary to each other and hence gives accessory information for better diagnosis. It is difficult to combine both modalities, technically and clinically than it was expected. Different researches are still going on to evaluate the comparison of PET/MRI with PET/CT and diffusion-weighted MRI or their combination. This review article discusses the technical aspect as well as its clinical application in head and neck cancer cases.